Creating interior atmosphere mise-en-scene and interior design - Whitehead, Jean (Bloomsbury Visual Arts, 2018)
"This book sets out to explore the creation of interior atmosphere as seen through the lens of mise-en-scène. You will learn how this film theory informs the concept of 'staged space' translated through the narrative and expressive qualities of a particular scene"--Provided by publisher.